Advances in Microfluidic Blood–Brain Barrier (BBB) Models. Issue 12 (December 2019) - Oddo, Arianna; Peng, Bo; Tong, Ziqiu; Wei, Yingkai; Tong, Wing Yin; Thissen, Helmut; Voelcker, Nicolas Hans
Abstract : Therapeutic options for neurological disorders currently remain limited. The intrinsic complexity of the brain architecture prevents potential therapeutics from reaching their cerebral target, thus limiting their efficacy. Recent advances in microfluidic technology and organ-on-chip systems have enabled the development of a new generation of in vitro platforms that can recapitulate complex in vivo microenvironments and physiological responses. In this context, microfluidic-based in vitro models of the blood–brain barrier (BBB) are of particular interest as they provide an innovative approach for conducting research related to the brain, including modeling of neurodegenerative diseases and high-throughput drug screening. Here, we present the most recent advances in BBB-on-chip devices and examine validation steps that will strengthen their future applications. Highlights: Microfluidic-based blood–brain barrier-on-chip (μBBB) technology is a powerful approach to study the physiological function of the BBB in vitro and to facilitate drug discovery targeting brain disorders. Mimicry of the complexity of multiple cell crosstalk and thin extracellular matrix as basal membrane are essential but challenging. Different biomaterials and chip designs have been explored in the fabrication of μBBBs. Other key features such as shear stress, cell type/origin, and cell co-culture spatial configuration must be carefully controlled and selected. Appropriate BBB permeability assays and parameters (e.g., TEER measurement, small molecule drugs, and fluorescent probes) should be standardized and compared with in vivo data. μBBBs hold great potential in disease modeling, drug discovery, neurotoxicity screening, and personalized medicine applications.